Molecular Dynamics Simulation of SARS-CoV-2 E Ion Channel: The Study of Lone Protein and its Conformational Changes in Complex with Potential Cage Inhibitors - Shiryaev, Vadim Andreevich; Ivleva, Elena Alexandrovna; Zaborskaya, Maria Sergeevna; Tkachenko, Ilya Michailovich; Osyanin, Vitaly Alexandrovich; Klimochkin, Yuri Nikolaevich (Current Computer - Aided Drug Design, 2025)
BackgroundThe coronavirus E ion channel has previously been studied as a potential target for antiviral therapy, with several compounds found to bind to the channel. Since, these compounds have low activity, searching for effective E ion channel inhibitors of great importance.ObjectiveThis study aimed to develop a computational approach for designing ligands for the coronaviral E ion channel and identify potential inhibitors based on this approach.MethodsThe structure of the E-ion channel was refined using molecular dynamics, and the pore responsible for binding cage compounds was selected as the inhibitor-binding site. Potential inhibitor structures were identified using molecular docking, and their binding was confirmed using molecular dynamics simulations.ResultsA number of potential SARS E ion channel inhibitors have been identified, and the binding modes and possible mechanisms of action of these inhibitors have been clarified.ConclusionThis study presents a computational approach that can be used to design ligands for E ion channels and identify potential inhibitors, providing valuable insights into the development of new antiviral therapies. The behavior of the E protein pentamer of SARS-CoV-2 in its native environment was investigated using Molecular Dynamics (MD), resulting in an equilibrated structure that could be used to develop new inhibitors through molecular docking. Simulation of the MD of E-channel complexes with amantadine analogues allowed for the identification of the main types of ligand-protein interactions that are responsible for the good binding of ligands within the channel's inner chamber.
Keywords: molecular dynamics